Finite Element Modelling and Elasto-Plastic Analysis of RHS Double and Single Chord T-Joints - Shehata, Ahmed Ahmed Atif (My University, 1983)
A research program is presented to investigate the behaviour of rectangular hollow section (RHS) T-joints in the elasto-plastic range of loading. The study includes the determination of both rotational and punching shear stiffnesses and strengths of the RHS T-joints due to branch moment or punching shear or a combination of both. The determined joint characteristics are then incorporated into an elasto-plastic analysis of Vierendeel trusses composed of RHS members.
Two different joint types have been analyzed, the double chord T-joint and the single chord type. In both cases, the joint is modelled by the chord top flange treated as a thin plate loaded on the perimeter of a rigid inclusion and restrained by coupled translational and rotational springs along its longitudinal edges. These springs simulate the restraining effect of the side walls and connecting bottom flange. Transverse edges, some distance from the joint, are taken as simply supported.
The proposed finite element formulation incorporates rectangular plate, beam and boundary spring elements. The formulation considers both bending and in-plane actions. Material nonlinearities of the joint are assumed to be adequately represented by the Von-Mises yield criterion and the associated flow rule. While geometric nonlinearities have been neglected, this assumption is reasonable for the range of deformations deemed important in this study.
A parametric analysis has been undertaken for each of the double chord and single chord joints under either branch moment or punching shear. Each analysis considers the effect of each of five non-dimensiononal geometric parameters. One of the parameters, considered, is used to study the stiffening effect of a reinforcing flange plate. Results of the analysis are presented in the form of non-dimensionalized load-deformation (M-Φ and P-δ) curves.
A standardization procedure has been used to develop generalized (M-Φ and P-δ) formulae, based on the parametric analyses. In addition, formulae for the joint stiffness and strength, in terms of its geometry, are presented for each case.
When the joints are analyzed under combined loading, the branch moment and punching shear are applied in different ratios. The results are presented in the form of interaction equations.
Next, the joint characteristics have been incorporated in an elasto-plastic finite element analysis of Vierendeel trusses. The effect of the joint flexibility on the truss behaviour is investigated. Also considered is a comparison between trusses possessing single chords and those possessing double chords.
Another aspect of this investigation is to predict upper bound capacities for the double chord joints due to branch moment or punching shear. The yield line theory has been utilized for this purpose.
The experimental part of the study involves the testing of ten double chord joints. Results of these tests along vith other available experimental data are used in examining the validity of the analytical models that have been developed.
Keywords: Civil Engineering; Civil Engineering